HUMAN RESOURCES TRAINING AND DEVELOPMENT IN THE DIGITAL ERA - Sudrajat, Jajat; Adi Permana, Ibar (International Journal of Law Social Sciences and Management, 2024)
This article raises the theme of the importance of training and development of Human Resources (HR) in the digital era. Rapid technological changes require organizations to continue developing employee skills to be able to adapt to changing work environments. We discuss key concepts related to HR training and development, including the use of digital technology, innovative learning strategies, and the integration of artificial intelligence in development programs. Additionally, this article highlights the strategic role of training in increasing productivity, employee satisfaction, and an organization's ability to compete in the digital marketplace. By exploring various aspects of HR training and development in the digital era, this article provides an in-depth look at how organizations can optimize the potential of their human resources in the face of the ongoing technological revolution. An effective HR training and development strategy in the digital era must be personalized, technology-based, and support a culture of continuous learning. By implementing the right strategies, organizations and individuals can ensure they have the skills and knowledge needed to achieve success in the digital era